TEACHING DESCRIPTIVE TEXT USING YOUTUBE CHANNEL: AN ANALYSIS OF ENGLISH STUDENTS’ PERCEPTION - Mahmud Adi Syahputra; Ani Agustiyani; Maria Yosephine Widarti Lestari (STKIP Subang, 2023)
This study aimed to analyze English students' perceptions regarding the use of YouTube channels as a teaching tool for descriptive text in a seventh-grade class at SMP N 37 Semarang. Data was collected through the distribution of a questionnaire to the students. The study employed a quantitative approach, analyzing the responses obtained from the questionnaire. The findings indicate that YouTube offers numerous benefits in terms of enhancing students' writing skills and expanding their vocabulary. Furthermore, the use of YouTube as an instructional tool serves as a motivational factor and boosts students' engagement in the subject matter. The availability of visually appealing videos with subtitles provides additional support for students to comprehend the content effectively. Moreover, the accessibility of YouTube enables students to access learning materials both inside and outside the classroom, facilitating flexible and convenient learning experiences. Overall, the research underscores the positive impact of incorporating YouTube as a medium for descriptive text learning, showcasing its potential in improving students' learning outcomes and fostering their active participation in the subject.